Curative effect of pterygium resection and autologous limbal stem cell transplantation combined with amniotic membrane transplantation in the treatment of pterygium - Yan-Xi Wang (Press of International Journal of Ophthalmology (IJO PRESS), 2021)
AIM: To observe the curative effect of pterygium resection and autologous limbal stem cell transplantation(LSCT)combined with amniotic membrane transplantation(AMT)in the treatment of pterygium.METHODS: Totally 177 patients(187 eyes)with pterygium treated in ophthalmology clinic of the hospital between January 2017 and January 2020 were selected and randomly divided into group A(59 cases, 64 eyes), group B(59 cases, 60 eyes), and group C(59 cases, 63 eyes). All were treated with pterygium resection. On this basis, patients in the three groups were treated with autologous LSCT, AMT, and autologous LSCT combined with AMT, respectively. All subjects were followed up for 12mo after surgery. Visual acuity, corneal epithelial repair, and neovascularization of the three groups were comparatively analyzed. Postoperative recurrence rate, ocular symptoms, complications, and survival of grafts were statistically analyzed.RESULTS: Visual acuity changes and repair time of corneal epithelial defect showed no statistically significant difference among the three groups(P>0.05). 1mo after surgery, the corneal fluorescein staining(FL)value of group C was significantly lower than that of group A or group B(all P<0.05). No angiogenesis or recurrent true pterygium was observed. 6mo and 12mo after surgery, the grades of conjunctival fibroplasia in group A and group C were significantly different from that in group B(P<0.05). There was no statistically significant difference in the wet length of the filter paper in Schirmer I test in terms of time, inter-group and interaction effects(P>0.05). 1mo after surgery, the tear film breakup time(BUT)of group C was significantly longer than that of group A or group B(all P<0.05). There were different degrees of conjunctival edema in the three groups after surgery, which disappeared within 2wk after suture removal. Grafts all survived, vascularization of amniotic membrane grafts ended.CONCLUSION:Autologous LSCT, AMT and autologous LSCT combined with AMT all are effective in the treatment of pterygium. However, autologous LSCT combined with AMT can achieve better short-term effect, with milder conjunctival fibroplasia and dry eye symptoms.